The Effect of Jigsaw Strategy with Picture as Media Towards Student’s Reading Comprehension of Recount Text at Thent-Grade of Darul Fattah Islamic Boarding School - Jannah, Wirdatul; Marleni, Lusi; Ayu, Citra (Journal of English Language and Education, 2026)
This research was conducted based on the observation that many students experience difficulties in comprehending recount texts. A quasi-experimental design was employed involving an experimental group taught using the Jigsaw strategy with picture media and a control group taught using conventional methods. The population consisted of tenth-grade students of Darul Fattah Islamic Boarding School, with 40 students selected as the sample. A multiple-choice reading comprehension test was administered as pre-test and post-test, and the data were analyzed using an independent samples t-test. The findings revealed that the experimental group showed significantly better improvement than the control group. The results indicate that the Jigsaw strategy with picture media effectively enhances students’ reading comprehension of recount texts and can be considered an alternative approach in teaching reading.